STRATEGI PEMURIDAN DI FAMILY CARE YANG EFEKTIF UNTUK MENINGKATKAN KUANTITAS JEMAAT DAN IMPLEMETASINYA DI GEREJA BETHEL INDONESIA TABGHA SEKUPANG - Pranada Pane; Samuel Tampubolon; Delismawati Sianturi (JURNAL TABGHA, 2023)
Discipleship is a task that must be carried out by the church. Discipleship has an understanding as a pattern of discipling or teaching and being discipled again to become similar to Christ, this pattern forms a chain that cannot be broken. Family Care is an appropriate and lively place where the discipleship process takes place and produces productive and effective students in shepherding God's people entrusted to a local church. Discipleship in Family Care is discipleship based on the word of God and aims to mature spiritually and make people worthy of God. And in carrying out discipleship it is very important to use a strategy. Strategies in discipleship in Family Care will make discipleship more effective and make it easier to achieve the goals or objectives to be achieved. The presence of Family Care members at the Sunday service has greatly impacted the growth in the quantity of congregations at the main service and also at the services of the Bethel Indonesia Tabgha Sekupang Church. Family Care as the spearhead of soul harvesting plays a very important role in increasing the quantity of congregations at Bethel Indonesia Tabgha Sekupang Church.